A streak length‐based method for quantifying red blood cell flow in skeletal muscle arteriolar networks. (22nd February 2019) - Goldman, Daniel; Farid, Zahra; Jackson, Dwayne N.
Abstract: Objective: To develop an experimental method to quantify RBC flow throughout skeletal muscle arteriolar networks. Methods: Data on arteriolar geometry were obtained using IVVM of the rat GM. RBC velocities and number densities were also obtained during these experiments using fluorescently labeled RBCs. Arteriolar and RBC data were combined to estimate blood volume flow rates, H T and H D values, and RBC volume flow rates. Validation of hematocrit and RBC flow results was performed at arteriolar bifurcations using both mass balance and comparisons to an established model of the PS effect. Results: Estimated H T values were within the expected range (6%‐34%) for the arterioles considered (29‐130 μm). RBC mass balance error was 18 ± 16% (mean ± SD, n = 7 bifurcations). RBC outflow from diverging bifurcations as a function of RBC inflow was given by Y = 0.986* X + 0.331 with R 2 = 0.987. Outflow H T as a function of the PS prediction was given by Y = 1.034* X + 0.004 with R 2 = 0.691. RBC outflow as a function of the prediction was given by Y = 0.917* X + 0.804 with R 2 = 0.891. Conclusions: An experimental method has been developed and validated that can easily and accurately quantify RBC flow distribution in large skeletal muscle arteriolar networks and provides direct estimates of H T values.